1981
DOI: 10.1099/0022-1317-57-1-95
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatitis B Virus-specific DNA in the Genomes of Human Hepatocellular Carcinoma and Liver Cirrhosis Tissues

Abstract: SUMMARYHepatitis B virus-related DNA was detected in the chromosomal DNA of three out of seven hepatocellular carcinomas and two out of five cirrhosis samples examined, by means of the blot-hybridization technique, described by Southern (1975). The integration patterns were not identical but some similarities raise the question of whether there are some preferred sites of viral integration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
50
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 22 publications
3
50
0
Order By: Relevance
“…It has been proposed that the removal of cccDNA occurs by hepatocyte turnover, and that dilution of cccDNA copy numbers in dividing hepatocytes results in eventual segregation of uninfected progeny cells (12). Alternatively, uninfected hepatocytes may arise by differentiation of uninfected progenitors (13) or be generated through a slow loss of cccDNA from infected hepatocytes (14,15).During hepadnavirus infection, a small fraction of hepatocytes undergo recombination with viral DNA molecules in the nucleus and acquire an integrated viral DNA that may be stably retained in that hepatocyte lineage (16)(17)(18)(19)(20). The common precursor to integrated viral DNA is a full-length linear double-stranded DNA, with a left end just upstream of the viral core gene, that is formed as a by-product of viral genome synthesis (21,22).…”
mentioning
confidence: 99%
“…It has been proposed that the removal of cccDNA occurs by hepatocyte turnover, and that dilution of cccDNA copy numbers in dividing hepatocytes results in eventual segregation of uninfected progeny cells (12). Alternatively, uninfected hepatocytes may arise by differentiation of uninfected progenitors (13) or be generated through a slow loss of cccDNA from infected hepatocytes (14,15).During hepadnavirus infection, a small fraction of hepatocytes undergo recombination with viral DNA molecules in the nucleus and acquire an integrated viral DNA that may be stably retained in that hepatocyte lineage (16)(17)(18)(19)(20). The common precursor to integrated viral DNA is a full-length linear double-stranded DNA, with a left end just upstream of the viral core gene, that is formed as a by-product of viral genome synthesis (21,22).…”
mentioning
confidence: 99%
“…1 In this context, it has been shown that most HBV-related hepatocellular carcinomas contained integrated viral DNA. 2 Four genes are encoded by the viral genome: S/preS, C/preC, P, and X. 3 The X gene encodes a 17-kd protein, termed HBx, that has been shown to function as a transcriptional trans-activator of a variety of viral and cellular promoter/enhancer elements.…”
mentioning
confidence: 99%
“…Thus, HBV-specific DNA is present not only in nuclei of the cells (Marion et aL, 1980;Chakraborty et al, 1980;Brechot et al, 1980;Edman et aL, 1980;Koshy et al, 1981) but also in a non-chromosomal form. Since chromosomal DNA of these cells contains integrated virus genes not only for HBsAg (which is synthesized in the cells) but very probably the complete virus genome (Marion et al, 1980), one could envisage the presence of additional HBV sequences also in the beta particle DNA.…”
mentioning
confidence: 99%
“…Particulate material from the latter was further concentrated by pelleting through a 10% sucrose cushion and is subsequently referred to as beta particles. The beta particles as well as fractions containing nuclei or mitochondria were submitted to a gentle DNA extraction procedure (Koshy et al, 1981). Two recombinant plasmids (Burrell et al, 1979), pHBV 20 [with a 650 base pair (bp) insert specific for HBsAg] and pHBV 8.2.51 (with a 550 bp insert specific for HBcAg), have been kindly provided by Dr K. Murray, Heidelberg, F.R.G.…”
mentioning
confidence: 99%
See 1 more Smart Citation